A COMPREHENSIVE STUDY OF KUSTHA (SAUSSUREA LAPPA (C.B. CLARKE) IN BRIHATTRAYI AND LAGHUTTRAYI - Kiran, *Vahisht; D.C., Singh; Vivek, Thakur (AYUSHDHARA, 2016)
Brihattrayi (Greater triad) and Laghuttrayi (Lesser triad) are excellent, highly esteemed and extensively used sources of Ayurvedic knowledge. Brihattrayi comprises Charaka samhita, Sushruta samhita and Astanga Hridaya and Laghuttrayi comprises Madhava nidana, Sharangdhar samhita and Bhava prakasha. Ayurveda delineates the uses of Kustha (Saussurea lappa (C.B. Clarke) for the management of different diseased conditions. Most of the Samhita Grantha have mentioned it in the treatment of Kustha, Shvitra (skin disease), Vata vyadhi (epilepsy), Arsha (piles), Mutrakricha (difficulty in micturition), Jvara (fever) and Vrana prasadana (wound healing). This article reviews the various references of Kustha in Brihattrayi and Laghuttrayi, regarding its different formulations and its prime therapeutic indications.